STRATEGI PEMASARAN PUFF PASTRY DENGAN DEKORASI KEKINIAN DALAM MENINGKATKAN OMSET NC RESTO - Wiwin Kurniasih, Imas; Bambang Nurcahya, Said (Jurnal Perhotelan dan Pariwisata, 2022)
Vocational education is education aimed at honing students towards practicum, this higher education makes the mastery of certain applied skills aimed at making students master the applied practice in the field, providing certain skills that are carried out for students to become members of the community who are capable as professionals in implementing and disseminating technology to improve the economy of life. Polytechnics are educational technology institutions and operate at the higher education level and use majors or diploma programs that focus on training. Pajajaran Polytechnic ICB Bandung, a form of private university located in Bandung, West Java, has study programs in Hospitality, Finance and Banking, Accounting, Computer Engineering, and Digital Business Office Administration. Pajajaran Polytechnic ICB Bandung is the oldest polytechnic in Bandung which has been established for more than 25 years and has graduated thousands of reliable human resources. The Hospitality Diploma Program at Pajajaran Polytechnic is one of the Study Programs that provides pastry & bakery courses. This study uses descriptive methods that discuss digital marketing strategies using social media, marketplaces and designing contemporary packaging, as well as cake decorations that have Sundanese characteristics. In product presentation and cake box design that presents Sundanese characteristics, it is hoped that it will attract new customers, especially millennials